Quantitative and qualitative impairments in dendritic cell subsets of patients with ovarian or prostate cancer. (August 2020) - Mastelic-Gavillet, Beatris; Sarivalasis, Apostolos; Lozano, Leyder Elena; Wyss, Tania; Inoges, Susana; de Vries, Ingrid Jolanda Monique; Dartiguenave, Florence; Jichlinski, Patrice; Derrè, Laurent; Coukos, George; Melero, Ignacio; Harari, Alexandre; et al.
Abstract: Background: Dendritic cells (DCs) are the most efficient antigen-presenting cells, hence initiating a potent and cancer-specific immune response. This ability (mainly using monocyte-derived DCs) has been exploited in vaccination strategies for decades with limited clinical efficacy. Another alternative would be the use of conventional DCs (cDCs) of which at least three subsets circulate in human blood: cDC1s (CD141 bright ), cDC2s (CD1c + ) and plasmacytoid DCs. Despite their paucity, technical advances may allow for their selection and clinical use. However, many assumptions concerning the DC subset biology depend on observations from mouse models, hindering their translational potential. In this study, we characterise human DCs in patients with ovarian cancer (OvC) or prostate cancer (PrC). Patients and methods: Whole blood samples from patients with OvC or PrC and healthy donors (HDs) were evaluated by flow cytometry for the phenotypic and functional characterisation of DC subsets. Results: In both patient groups, the frequency of total CD141 + DCs was lower than that in HDs, but the cDC1 subset was only reduced in patients with OvC. CD141 + DCs showed a reduced response to the TLR3 agonist poly (I:C) in both groups of patients. An inverse correlation between the frequency of cDC1s and CA125, the OvC tumour burden marker, was observed. Consistently, high expression of CLEC9A in OvC tissue (The Cancer Genome Atlas data set) indicated a better overall survival. Conclusions: cDC1s are reduced in patients with OvC, and CD141 + DCs are quantitatively and qualitatively impaired in patients with OvC or PrC. CD141 + DC activation may predict functional impairment. The loss of cDC1s may be a bad prognostic factor for patients with OvC. Highlights: The frequency of cDC1s is reduced in patients with ovarian cancer (OvC) but not in patients with prostate cancer (PrC). Frequency and function of CD141 + dendritic cells (DCs) are reduced in OvC and PrC. The basal activation of CD141 + DCs is increased in OvC and PrC. The activation of CD141 + DCs inversely correlates with their frequency and function. Reduced frequency of cDC1s may be associated with worse prognosis in OvC.